Risk factors for coexisting deep endometriosis for patients with recurrent ovarian endometrioma - Du, Yongjiang; Hu, Changchang; Ye, Chaoshuang; Wu, Ruijin (Frontiers in Surgery, 2022)
Aim: The aim of this study was to assess the risk factors for coexisting deep endometriosis (DE) in patients with recurrent ovarian endometrioma (OE). Methods: We retrospectively reviewed 151 recurrent OE patients who had been diagnosed of OE but not DE at the time of their first surgery and then received a second surgery for recurrent endometriosis with or without DE. Their clinical characteristics at the time of the first and second surgeries were collected. Univariate and multivariate logistic regression analyses were conducted to identify potential risk factors for coexisting DE in patients with recurrent OE. Results: Among the 151 recurrent OE patients, 46 were diagnosed of DE during the recurrent surgery and included in the DE group, while the remaining 105 patients were included in the non-DE group. In univariate analysis, there were significant differences in terms of uterine retroversion during the primary surgery and the follow-up time after the primary surgery between the DE and non-DE groups. The multivariate analysis also showed that both uterine retroversion and the follow-up time (≥5 years) were associated with the coexistence of DE during the recurrent surgery. The odds ratio (OR) for uterine retroversion was 3.72 (95% confidence interval [CI] 1.62-8.53), and the OR for follow-up time (≥5 years) was 5.03 (95% CI 2.29-11.02). Conclusions: Our study suggested that for recurrent OE patients, uterine retroversion during the first surgery and a follow-up time of at least 5 years are risk factors for the coexistence of DE in recurrent surgery, early prevention and full preparation before the recurrent surgery should be emphasized in these conditions.